THE IMPLEMENTATION OF COMMUNICATIVE LANGUAGE TEACHING PRINCIPLES IN TEACHING BUSINESS LETTER WRITING AT GENTA ENGLISH COURSE - Asrotinengseh, Asrotinengseh; Sulistyanto, Irwan (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2022)
Letter writing is one of the communication form that only can be done by writing. writing skill is skill that can not be gotten by naturally, unlike speaking. White in Khoo (1981) writing is not natural talent. Due to the difficulty, CLT is one of teaching English approaches that highly recommended that has goal to develop the student’s communicative both in speaking and writing. The aim is to identify the teaching at GENTA English course in teaching business letter writing class, first, about the process of teaching, the obstacles, the factors obstacles, and the strategies to solve the obstacles. The design of this research is qualitative descriptive, the qualitative method employed for analyzing the implementation of CLT principles in teaching business letter writing at GENTA English Course. The imstruments used to collect the data are: interview guide line, observation chceklist, and documentation. The result for different finding, (1) The process which includes the preparation (syllabus, lesson plan, material, and attendance list), implementation (pre-teaching, whilst- teaching, and post-teaching), and evaluation, (2) the obstacles faced by teachers and students: some groups did not work significantly, time is sometimes over, the students are too noisy, (3) the factors caused the obstacles faced by teachers and students: the random grouping, time management, the topic is too interesting, students are enjoying the topic, and (4) the strategies to solve the obstacles: teacher may do the grouping considering the active students as the leading agent of each group, teacher should carefully plan the time management, teacher may give some limitations to the students’ participation in the classroom, and add more meetings so that the goals are achieved.